EVOLUSI TEKNOLOGI ANIMASI DIGITAL: TINJAUAN LITERATUR TERHADAP PERKEMBANGAN METODE DAN TEKNIK RENDERING DALAM INDUSTRI KREATIF - Trianggulo Pundi Pranoto (PT. Hasba Edukasi Mandiri, 2026)
This research examines the evolution of digital animation technology through comprehensive literature review of rendering methods and techniques development in creative industries. Utilizing qualitative approach with library research methodology, this study analyzes paradigmatic transformation from conventional production methodologies toward integrated systems based on advanced technology. Findings indicate that implementation of pose-to-pose methods in cinematic animation has provided revolutionary precision control, while integration of virtual reality technology and real-time rendering algorithms has optimized visual quality with doubled computational efficiency. Cloud computing technology adoption has democratized access to high-end rendering infrastructure, enabling small-scale studios to compete through affordable computational capacity rental models. Production pipeline transformation from linear to parallel processing has enhanced creative efficiency and facilitated global collaboration. Indonesian animation industry requires comprehensive recovery strategies through government intervention in work project provision, financial support, and protective policies for sustainable growth.